(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Typhoid fever is a severe, potentially mortal multisystem illness caused by Salmonella typhi, and less often by S. paratyphi A, S. paratyphi B and S. paratyphi C. The Purpose of the current study is to find out the current in vitro antimicrobial susceptibility patterns of clinical isolates against the anti-typhoid drugs. In the current study we extracted a total 244 Typhoid Salmonellae from 6117 blood cultures received from Medical Department of Khyber teaching hospital Peshawar From July 2020 to October 20221. Further all Typhoid Salmonellae isolates were processed for identification using API & serological tests. Then Drug susceptibilities were performed as per CLSI 2012 criteria by Kirby-bauer disc diffusion and MIC’s of selected isolates. The Current study result show that S.typhi (83) & S.paratyphi A (85) were isolated in almost equal number. Predominantly males between 15-30 years were affected. Patients between 1-20 years had S.typhi as the predominant organism. Combined susceptibilities of Typhoid Salmonellae showed Chloramphenicol (75.9%) as the most sensitive antibiotic, followed by Amoxicillin (73.2%) and SXT (68%). More than 95% of resistance was seen with Quinolones, both in S.typhi and S.paratyphi A. Third generation Cephalosporins (Ceftriaxone) and Carbapenems revealed 100% sensitivity. Multi Drug Resistant isolates (25.2%) & Extreme Drug Resistant isolates (15.02%) were all S.typhi. 24% of isolates were β-lactamase producers whereas no ESBL production was seen. Azithromycin susceptibility was also done but could not be interpreted due to non-availability of interpretive guidelines. From the current study we conclude that decline of susceptibility pattern of first line anti-typhoid drugs noted, but still don’t qualify as empirical drugs. At present third generation Cephalosporins and Carbapenems are the only empirical treatment options. Flouroquinolones is no more recommended for the treatment of typhoid fever. As no interpretive guidelines are available for Azithromycin, so it can be evaluated in future on the basis of its clinical efficacy in therapeutic trials and available guidelines.